Reference Data of Phase Angle Using Bioelectrical Impedance Analysis in Overweight and Obese Chinese - Fu, Luo; Ren, Zhengyun; Liu, Xiaoxiao; Wu, Nianwei; Zhao, Kang; Luo, Guangping; Yang, Huawu; Zhang, Yuanchuan; Yan, Tong; Liu, Yanjun; Zhang, Tongtong (Frontiers in Endocrinology, 2022)
Introduction Phase angle (PhA) is a ratio of reactance and resistance {arctangent (reactance (Xc)/resistance (R)) × (180°/π)}, which can be obtained by bioelectrical impedance analysis (BIA). PhA indicates cellular health and integrity, and it is also considered as a prognostic tool in medical disorders and an indicator of nutritional status (especially of muscle quality) in patients with obesity. However, PhA has limited usefulness in clinical practice because of a lackness of reference values for Chinese overweight and obese populations. The main aim of this study was to show PhA reference data in different age and BMI groups by sex. In addition, we also study the association of age, sex, and BMI on PhA. Methods A total of 1729 overweight and obese participants were included in this study. PhA and body composition were measured using segmental multifrequency BIA. Differences in mean values for variables were tested by one-way analysis of variance. Multiple regression analysis was used to assess the associations of PhA with age, sex and BMI. Results Multiple regression analysis showed that age, sex and BMI were significant (P < 0.05) independent influence factors of PhA in Chinese overweight and obese adults when age and BMI were continues variables. The mean PhA value for all participants was 5.5°. Mean BMI, age, weight, height and 50kHz-PhA were significantly higher (P < 0.001) in male participants than female ones. In age groups and BMI groups, mean 50kHz-PhA was significantly higher (P < 0.005) in male participants than female ones. When age groups and BMI groups were categorical variables, multiple regression analysis showed that different age groups (46–55 years and ≥ 56 years) had a significantly lower (P < 0.005) PhA as compared with the baseline group (18-25 years) and different BMI groups (≥ 28 kg/m2) had a significantly higher (P < 0.05) PhA as compared with the baseline group (24–27.9 kg/m2). Conclusion PhA differed according to age, sex and BMI. Reference data in this study can be taken into consideration when deriving the reference values for overweight and obese Chinese populations.